2012
DOI: 10.1111/j.1524-4725.2012.02500.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial of Four Ablative Fractionated Lasers for Photoaging: A Quadrant Study

Abstract: Fractionated ablative lasers reliably result in improvement in photoaging. Despite marketing claims, no statistically significant differences were found in outcomes, pain during treatment, or histologic findings. Even with experienced users, significant adverse reactions are possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Many types of fractionated laser treatment modalities currently exist, including erbium-doped yttrium aluminum garnet (Er:YAG) and yttrium scandium gallium garnet (YSGG). A study by LaTowsky and colleagues showed statistically similar effectiveness amongst four fractional laser devices up to 6 months post treatment, including Active and Deep (CO 2 ), Fraxel Repair (CO 2 ), Quadralase (CO 2 ), and Pearl (YSGG) [77,78]. Fraxel Repair pain scores ranged higher than other devices and resulted in the most pinpoint bleeding, but was the most time efficient device and produced the highest patient satisfaction at 1 month post treatment; Active and Deep also caused pinpoint bleeding, but patients scored it highest for ease of healing and willingness to repeat treatment [79].…”
Section: Ablative Fractionated Photothermolysis (Afp)mentioning
confidence: 98%
“…Many types of fractionated laser treatment modalities currently exist, including erbium-doped yttrium aluminum garnet (Er:YAG) and yttrium scandium gallium garnet (YSGG). A study by LaTowsky and colleagues showed statistically similar effectiveness amongst four fractional laser devices up to 6 months post treatment, including Active and Deep (CO 2 ), Fraxel Repair (CO 2 ), Quadralase (CO 2 ), and Pearl (YSGG) [77,78]. Fraxel Repair pain scores ranged higher than other devices and resulted in the most pinpoint bleeding, but was the most time efficient device and produced the highest patient satisfaction at 1 month post treatment; Active and Deep also caused pinpoint bleeding, but patients scored it highest for ease of healing and willingness to repeat treatment [79].…”
Section: Ablative Fractionated Photothermolysis (Afp)mentioning
confidence: 98%